Synthesis and Crystal Structure of a Tetraazamacrocyclic Copper(II) Complex - Bi, Jian-Hong; Tao, Wen-Bo; Huang, Zi-Xiang; Bi, Wen-Tao (Asian Journal of Chemistry, 2010)
The copper(II) complex [CuL]·(ClO4)2 (L= 5,5,7,12,12,14- hexamethyl-1,4,8,11-tetrazamacrocyclotetradecane·2ClO4) has been synthesized and determined by X-ray diffraction. The crystal is monoclinic, space group P2(1)/n with unit cell parameters: a = 8.463(3)Å, b = 9.178(3)Å, c = 15.567(5)Å. α = 90º, β = 98.120(4)º, γ = 90º, v = 1197.0(6)Å3, z = 2, Dc = 1.518 Mg/m3, Mr = 546.93, F(000) = 574 and μ = 1.183 mm-1. The final R and wR are 0.0379 and 0.1034, respectively for 2705 observed reflections with I>2σ(I). The center copper(II) ion is four-coordinated in a slightly distorted square geometry.